2001
DOI: 10.7863/jum.2001.20.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of endometrial receptivity by transvaginal color Doppler and three‐dimensional power Doppler ultrasonography in patients undergoing in vitro fertilization procedures.

Abstract: The objective of this study was to investigate the usefulness of transvaginal color Doppler and three-dimensional power Doppler ultrasonography for the assessment of endometrial receptivity. A total of 89 patients undergoing in vitro fertilization procedures were evaluated for endometrial thickness and volume, endometrial morphology, and subendometrial perfusion on the day of embryo transfer. Neither the volume nor the thickness of the endometrium on the day of embryo transfer had a predictive value for concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
138
4
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(155 citation statements)
references
References 34 publications
9
138
4
4
Order By: Relevance
“…While in our study, we chose to consider only the endometrial thickness, both endometrial thickness and pattern are generally acknowledged as predictors of the outcome of pregnancy. 13 The endometrial thickness was measured in this study for a group of 50 fertile and 50 infertile females in all three phases of the menstrual cycle and the results were compared using p value. The mean ± standard deviation for endometrial thickness was higher in fertile females than infertile females in all the three phases of menstrual cycle (Graph 1, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…While in our study, we chose to consider only the endometrial thickness, both endometrial thickness and pattern are generally acknowledged as predictors of the outcome of pregnancy. 13 The endometrial thickness was measured in this study for a group of 50 fertile and 50 infertile females in all three phases of the menstrual cycle and the results were compared using p value. The mean ± standard deviation for endometrial thickness was higher in fertile females than infertile females in all the three phases of menstrual cycle (Graph 1, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Two parameters are considered to predict pregnancy: a) endometrial volume and b) (sub) endometrial flow. a) The first studies reported a good correlation between endometrial volume and pregnancy (31)(32)(33). Although it has been shown that the endometrium must attain at least 2.0-2.5 ml to achieve a pregnancy, recent studies did not confirm the relation between endometrial volume and pregnancy outcome (33)(34)(35)(36)(37).…”
Section: Endometrial Receptivitymentioning
confidence: 96%
“…Other investigators (Rinaldi et al,1996) observed correlations between a minimal endometrial thickness of 9-10 mm and higher implantation rates. Some authors (Kupesic et al,2001;Schild et al,2001) did not observe successful implantations when the endometrium was thinner than 7 mm.…”
Section: The Role Of Endometrial Structurementioning
confidence: 99%
“…The authors claimed that endometrial growth and its pattern during the controlled ovarian hyperstimulation did not influence on the implantation rate (Bassil,2001;Kupesic et al,2001;Rashidi et al,2005).…”
Section: Wwwintechopencommentioning
confidence: 99%